Konstruktivno socialno delo na Osnovni šoli Leskovec pri Krškem - Janušič, Daniela (Socialno delo, 2016)
For smooth functioning of all school activities, a lot of prevention work with children is needed, especially on the field of preventing violence. In this respect, the workshop entitled "No peer violence", organized by the Institute for psychological counceling projects, plays an important part at the Elementary School Leskovec pri Krškem. When children experience violence, they are therefore quicker to express their uneasiness and are more prone to solve conflicts with peers when they appear. By playing different roles in the workshop, they learn strategies that enable them to take a stand for themselves. As a result of the workshop, relationships among them improve. Teaching assistance to the Roma children is also organised, as it develops their learning skills but also connects the school with the pupils' families and their wider social environment. If we manage to engage all parts in the educational process (pupil, class teacher, teachers, parents, headmaster) and get their contributions, examples of good practice ensue. One such example is descirbed, involving a Rome girl who was prevented to attend school by her father.
Keywords: pupils; social work; socialno delo; učenci; Roma; Romi; peer violence; role play; vrstniško nasilje; preventiva; learning assistance; good practice; igranje vlog; učna pomoč; dobra praksa; Osnovna šola Leskovec pri Krškem